Odds of Achieving Target Serum Uric Acid Levels Among Gout Patients: The Role of Rurality in Outcomes and Treatment Adherence - S. Scott Sutton; Joseph Magagnoli; Tammy H. Cummings; James W. Hardin (SAGE Publishing, 2023)
Objective: The goal of this paper was to analyze patient outcomes related to gout treatment including, serum uric acid (sUA) measures and treatment adherence across patients in metropolitan, micropolitan or rural counties. Methods: We conducted a drug-disease cohort study among patients with gout initiating urate lowering therapy. The proportion of patients with sUA < 6 mg/dL at 1 year of follow-up is compared over the cohort groups using a chi-square test and adjusted logistic regression. Adherence to urate lowering therapy was calculated using the proportion of days covered (PDC). A T -test was used to compare the average PDC and an adjusted logistic regression model was used to estimate the odds of a PDC greater than 80%. Results: A total of 9922 patients were included in the study. Most patients were in a metropolitan (77.4%) area, followed by micropolitan (11.8%) and finally, (10.8%) in a rural area. We found no statistically significant difference among the proportion of patients achieving target sUA of <6 mg/dL, 37.17% among metropolitan patients, 38.9% among micropolitan patients, and 37.7% for those in a rural area, P -value = .502. The proportion of patients achieving 80% treatment adherence was 49.92% in the metropolitan, 51.78% in the micropolitan, and 55.05% in the rural areas, P -value = .005. Adjusted regression models showed no statistically significant difference in proportions achieving target sUA levels or 80% adherence. Conclusions: Urban patients treated for gout did not have better gout outcomes compared to rural patients. Future research should consider provider-based interventions to improve outcomes.